A Guttate Psoriasis That Tends to Spare Three Tattoos: A Macrophage Liaison. (13th September 2021) - Spyridonos, Panagiota; Zampeli, Vasiliki; Rapti, Sophia-Nefeli; Bassukas, Ioannis D.
Abstract : Induction of new psoriasis sites was reported in only a small amount of psoriasis patients undergoing tattooing, despite the intuitive belief that tattoo trauma might awaken the disease due to the isomorphic phenomenon of Koebner. In this case report, we discuss a patient who presented with a remarkable sparing of his three tattoo sites during a guttate psoriasis flare-up that was unrelated to tattooing. The spatial concordance of tattoo and psoriasis lesions was analyzed on clinical pictures of tattoo sites taken during the psoriasis episode. For the quantification of the spatial distribution of the psoriasis lesions, Voronoi diagrams were generated, and coefficients of variation and the two-sample t -test were employed to compare the distributions of Voronoi patch sizes in different settings. Compared to skin areas without tattoos, a tattoo introduced a higher variation in the sizes of the Voronoi patches centered around psoriasis lesions. Based on our findings, we would like to discuss the possible role of macrophages as the key cellular link in the complex pathophysiologic relationship between tattooing/tattoo and psoriasis. Taking into account the relationship of autophagy and psoriasis lesions, we propose the hypothesis that tattoos represent a "psoriasis-hostile" tissue environment pertained by a population of LAP active M2-polarized macrophages. Further clinical studies of the relationship of psoriasis lesions to the tattooed skin are needed and may provide important insights into the role of macrophages in the pathogenesis of psoriasis.